MINAT REMAJA TERHADAP KESENIAN DIKIA RABANO - Mulia Natasya; Rina Susanti (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
Dikia rabano art is an art with Islamic nuances located in Nagari Panampuang, Ampek Angkek District, Agam Regency West Sumatera. Dikia rabano art is a local cultural property that must be maintained and preserved by the community, especially teenagers. This art is practiced by men aged between 18 and 50 and is usually performed at weddings and the release of pilgrims. Dikia rabano art is usually held at home so that it becomes less attractive to young people and creates different views among young people, especially teenagers. The art of dikia rabano is assimilated with traditional Minangkabau philosophy, namely "adat basandi syarak, syarak basandi Kitabullah". The purpose of this study was to determine the factors that influence adolescents' interest in dikia rabano art and to find out their views on dikia rabano art. This study used a descriptive quantitative method with a sample of 75 adolescent respondents in Nagari Panampuang. Data collection is done by making a list of structured questions, observations and documentation. The results show that the dominant factors that influenced adolescents' interest in dikia rabano art are personal and family factors and adolescents had a negative view on dikia rabano art because it was unattractive and boring.